Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning. - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
Oligodendrocytes produce myelin for rapid transmission and saltatory conduction of action potentials in the vertebrate central nervous system. Activation of the myelination program requires several transcription factors including Sox10, Olig2, and Nkx2.2. Functional interactions among them are poorly understood and important components of the regulatory network are still unknown. Here, we identify Nfat proteins as Sox10 targets and regulators of oligodendroglial differentiation in rodents and humans. Overall levels and nuclear fraction increase during differentiation. Inhibition of Nfat activity impedes oligodendrocyte differentiation in vitro and in vivo. On a molecular level, Nfat proteins cooperate with Sox10 to relieve reciprocal repression of Olig2 and Nkx2.2 as precondition for oligodendroglial differentiation and myelination. As Nfat activity depends on calcium-dependent activation of calcineurin signaling, regulatory network and oligodendroglial differentiation become sensitive to calcium signals. NFAT proteins are also detected in human oligodendrocytes, downregulated in active multiple sclerosis lesions and thus likely relevant in demyelinating disease.
UnivIS-Import:2018-09-11:Pub.2018.med.IB.LPCIPDBI.nfatca

PBAF Subunit Pbrm1 Selectively Influences the Transition from Progenitors to Pre-Myelinating Cells during Oligodendrocyte Development - Waldhauser, Vanessa; Baroti, Tina; Fröb, Franziska; Wegner, Michael (Cells, 2023)
Oligodendrocyte development is accompanied by defined changes in the state of chromatin that are brought about by chromatin remodeling complexes. Many such remodeling complexes exist, but only a few have been studied for their impact on oligodendrocytes as the myelin-forming cells of the central nervous system. To define the role of the PBAF remodeling complex, we focused on Pbrm1 as an essential subunit of the PBAF complex and specifically deleted it in the oligodendrocyte lineage at different times of development in the mouse. Deletion in late oligodendrocyte progenitor cells did not lead to substantial changes in the ensuing differentiation and myelination processes. However, when Pbrm1 loss had already occurred in oligodendrocyte progenitor cells shortly after their specification, fewer cells entered the pre-myelinating state. The reduction in pre-myelinating cells later translated into a comparable reduction in myelinating oligodendrocytes. We conclude that Pbrm1 and, by inference, the activity of the PBAF complex is specifically required at the transition from oligodendrocyte progenitor to pre-myelinating oligodendrocyte and ensures the generation of normal numbers of myelinating oligodendrocytes.
CRIS-Team Scopus Importer:2023-07-28
Keywords: chromatin remodeling; glia; myelin; oligodendrocyte; polybromo-1

Publisher Correction: Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
The originally published version of this Article omitted Tanja Kuhlmann and Michael Wegner as jointly supervising authors. This has now been corrected in both the PDF and HTML versions of the Article.
EVALuna2:35744

Role of the Pbrm1 subunit and the PBAF complex in Schwann cell development - Polanetzki, Vanessa; Fröb, Franziska; Baroti, Tina; Schimmel, Margit; Tamm, Ernst R.; Wegner, Michael (Scientific Reports, 2022)
Myelin sheath formation in the peripheral nervous system and the ensuing saltatory conduction rely on differentiated Schwann cells. We have previously shown that transition of Schwann cells from an immature into a differentiated state requires Brg1 that serves as the central energy generating subunit in two related SWI/SNF-type chromatin remodelers, the BAF and the PBAF complex. Here we used conditional deletion of Pbrm1 to selectively interfere with the PBAF complex in Schwann cells. Despite efficient loss of Pbrm1 early during lineage progression, we failed to detect any substantial alterations in the number, proliferation or survival of immature Schwann cells as well as in their rate and timing of terminal differentiation. As a consequence, postnatal myelin formation in peripheral nerves appeared normal. There were no inflammatory alterations in the nerve or other signs of a peripheral neuropathy. We conclude from our study that Pbrm1 and very likely the PBAF complex are dispensable for proper Schwann cell development and that Schwann cell defects previously observed upon Brg1 deletion are mostly attributable to altered or absent function of the BAF complex.
CRIS-Team Scopus Importer:2022-02-25

The transcription factor Sox10 is an essential determinant of branching morphogenesis and involution in the mouse mammary gland - Mertelmeyer, Svenja; Weider, Matthias; Baroti, Tina; Reiprich, Simone; Fröb, Franziska; Stolt, Claus; Wagner, Kay Uwe; Wegner, Michael (Scientific Reports, 2020)
The high mobility group-domain containing transcription factor Sox10 is an essential regulator of developmental processes and homeostasis in the neural crest, several neural crest-derived lineages and myelinating glia. Recent studies have also implicated Sox10 as an important factor in mammary stem and precursor cells. Here we employ a series of mouse mutants with constitutive and conditional Sox10 deficiencies to show that Sox10 has multiple functions in the developing mammary gland. While there is no indication for a requirement of Sox10 in the specification of the mammary placode or descending mammary bud, it is essential for both the prenatal hormone-independent as well as the pubertal hormone-dependent branching of the mammary epithelium and for proper alveologenesis during pregnancy. It furthermore acts in a dosage-dependent manner. Sox10 also plays a role during the involution process at the end of the lactation period. Whereas its effect on epithelial branching and alveologenesis are likely causally related to its function in mammary stem and precursor cells, this is not the case for its function during involution where Sox10 seems to work at least in part through regulation of the miR-424(322)/503 cluster.
CRIS-Team Scopus Importer:2020-10-30

Transcription factor Sox10 induces the microRNAs miR-335, miR-338 and miR-155 to ensure correct timing of oligodendrocyte development - Küspert, Melanie; Reiprich, Simone; Cantone, Martina; Weider, Matthias; Baroti, Tina; Wittstatt, Jan; Vera, Julio; Wegner, Michael (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Transcription factor Sox10 regulates oligodendroglial Sox9 levels via microRNAs. - Reiprich, Simone; Cantone, Martina; Weider, Matthias; Baroti, Tina; Wittstatt, Jan; Schmitt, Christian; Küspert, Melanie; Vera, Julio; Wegner, Michael (Glia, 2017)
During development of myelin-forming oligodendrocytes in the central nervous system the two closely related transcription factors Sox9 and Sox10 play essential roles that are partly shared and partly unique. Whereas Sox9 primarily functions during oligodendroglial specification, Sox10 is uniquely required to induce terminal differentiation and myelination. During this process, Sox10 protein levels rise substantially. As this coincides with a reciprocal decrease in Sox9, we postulated that Sox10 influences Sox9 amounts in differentiating oligodendrocytes. Here we show that Sox9 levels are indeed inversely coupled to Sox10 levels such that Sox10 deletion in oligodendroglial cells evokes a reciprocal increase in Sox9. We furthermore provide evidence that this coupling involves upregulation of microRNAs miR335 and miR338 as direct transcriptional targets of Sox10. The two microRNAs in turn recognize the 3′-UTR of Sox9 mRNA and may thereby reduce Sox9 protein levels posttranscriptionally in oligodendroglial cells. Such a mechanism may enable oligodendroglial cells to adapt the ratio of both related Sox proteins in a manner required for successful lineage progression and differentiation. Mathematical modeling furthermore shows that the identified regulatory circuit has the potential to convert a transient stimulus into an irreversible switch of cellular properties and may thus contribute to terminal differentiation of oligodendrocytes.
EVALuna2:33479
Keywords: glia; HMG; miR338; oligodendrocyte; Sox

Transcription Factors Sox2 and Sox3 Directly Regulate the Expression of Genes Involved in the Onset of Oligodendrocyte Differentiation - Rupprecht, Jesse; Reiprich, Simone; Baroti, Tina; Christoph, Carmen; Sock, Elisabeth; Fröb, Franziska; Wegner, Michael (Cells, 2024)
Rapid information processing in the central nervous system requires the myelination of axons by oligodendrocytes. The transcription factor Sox2 and its close relative Sox3 redundantly regulate the development of myelin-forming oligodendrocytes, but little is known about the underlying molecular mechanisms. Here, we characterized the expression profile of cultured oligodendroglial cells during early differentiation and identified Bcas1, Enpp6, Zfp488 and Nkx2.2 as major downregulated genes upon Sox2 and Sox3 deletion. An analysis of mice with oligodendrocyte-specific deletion of Sox2 and Sox3 validated all four genes as downstream targets in vivo. Additional functional assays identified regulatory regions in the vicinity of each gene that are responsive to and bind both Sox proteins. Bcas1, Enpp6, Zfp488 and Nkx2.2 therefore likely represent direct target genes and major effectors of Sox2 and Sox3. Considering the preferential expression and role of these genes in premyelinating oligodendrocytes, our findings suggest that Sox2 and Sox3 impact oligodendroglial development at the premyelinating stage with Bcas1, Enpp6, Zfp488 and Nkx2.2 as their major effectors.
CRIS-Team Scopus Importer:2024-06-21
Keywords: glia; myelin; Nkx2.2; SoxB1 proteins; transcription factor; Zfp488